How to live : what the Rule of St. Benedict teaches us about happiness, meaning, and community - Valente, Judith (Hampton Roads Pub., 2018)
The Rule of St. Benedict arose from an era when a great civilization was threatened by violence, economic forces that favored the wealthy, political leaders that lacked the trust of the public, and rampant xenophobia. Similar to the anxieties and frustrations of the 6th century, we are living in a time where societies need to stress community over competition, consensus over conflict, simplicity over self gain, and silence over the constant chatter and distractions of our lives. In How to Live, Judith Valente explores the key elements of the rule and clearly demonstrates how incorporating this ancient wisdom can change the quality and texture of our lives offering a way forward from the divisions gripping our country. These fresh and profound explorations are inspiring and thoughtful, and will motivate readers to live a meaningful life.